Preparation method of electrolyte film for all-solid-state battery and all-solid-state battery
By using the combination of first and second solvent combinations in the full solid battery to regulate the state of the adhesive molecular segment, the nano -grade binder particles are formed, solving the problem of low -ion ion conductivity of solid electrolyte thin film, and increased the energy density of the battery. And security.
Patent Information
- Application Number
- CN202411468804.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-01-24
AI Technical Summary
The solid electrolyte film used in existing all-solid state batteries has a low ionic conductivity, which limits the energy density and safety of the battery.
By using the combination of first solvents and second solvents, the aggregation and precipitation state of the molecular segment of the adhesives are regulated to form a nano -level adhesive particles to improve the ion conductivity of the electrolyte film.
It significantly improves the ion conductivity of the electrolyte thin film, enhances the energy density and safety of the full solid battery, and avoids difficulty in the relocation of ion migration caused by bonding the coating method in the traditional wet coating method.
Smart Images

Figure BDA0005094894680000041 
Figure HDA0005094894900000011 
Figure HDA0005094894900000012
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of all-solid-state batteries, and in particular relates to a method for preparing an electrolyte film for an all-solid-state battery and an all-solid-state battery. Background Art
[0002] In liquid lithium-ion batteries, liquid esters are usually used as electrolytes, which makes traditional liquid electrolytes and corresponding lithium-ion batteries prone to combustion and explosion after being subjected to external thermal shock or mechanical shock. And because the electrochemical window of the electrolyte is narrow, after contacting the high-nickel positive electrode and low-potential negative electrode materials (such as Si, Li), a positive electrode electrolyte interface (CEI) or a solid electrolyte interface (SEI) will be formed, and the electrolyte will be continuously consumed; this also limits the further improvement of the energy density of liquid batteries. In all-solid-state batteries, the electrolyte in traditional liquid batteries is replaced by a non-volatile, non-flowing, and non-flammable solid electrolyte, which makes the all-solid-state battery have a certain improvement in safety compared to liquid lithium-ion batteries. At the same time, replacing the electrolyte block with a solid electrolyte film can significantly reduce the proportion of inactive substances in the battery, thereby improving the energy density of the all-solid-state battery.
[0003] At present, the solvent wet coating method is commonly used to prepare solid electrolyte films. However, the electrolyte film prepared by this method has the problem of low ion conductivity. The reason is that the main steps of wet coating are: dissolving the binder (such as polyvinylidene fluoride, styrene butadiene latex) in an organic solvent to form a sol, and then mixing the above sol with solid electrolyte particles to form a slurry; then the solvent is evaporated through a drying step, and the binder is precipitated on the surface of the solid electrolyte to form a continuous binder network, thereby bonding the electrolyte particles together to form a film. Figure 1 As shown, in the prepared slurry, the binder is dissolved in the solvent to form dispersed polymer segments; during the drying process, the binder polymer segments precipitate and adsorb on the surface of the electrolyte particles, which is equivalent to forming a layer of polymer coating on the surface of the electrolyte particles.
[0004] However, existing binder polymers usually do not have the ability to transport lithium ions, which causes the ionic conductivity of the electrolyte film to be significantly lower than that of the electrolyte powder. Summary of the invention
[0005] In view of the main defects of the above-mentioned prior art, the present invention provides a method for preparing an electrolyte film for an all-solid-state battery and an all-solid-state battery. The method of the present invention can produce an electrolyte film with good ionic conductivity, which is conducive to the application in all-solid-state batteries.
[0006] The present invention provides a method for preparing an electrolyte film for an all-solid-state battery, comprising the following steps:
[0007] dissolving a binder in a first solvent to form a first polymer solution having a second Virial coefficient greater than 0;
[0008] mixing electrolyte particles with the polymer solution to form an electrolyte slurry;
[0009] Applying the electrolyte slurry on a substrate to form a wet film;
[0010] uniformly covering the wet film with a second solvent by coating, and drying with a hot roller to obtain an electrolyte film for an all-solid-state battery;
[0011] The boiling point of the second solvent is higher than that of the first solvent. The second solvent and the first solvent are mixed to dissolve the binder to form a second polymer solution. The second Virial coefficient of the second polymer solution is smaller than the second Virial coefficient of the first polymer solution.
[0012] Preferably, the first solvent and the second solvent are both low-polarity or non-polar organic solvents; the first solvent is a substituted or unsubstituted aromatic hydrocarbon substance, an amide substance or a sulfoxide substance; the second solvent is a straight-chain alkane, a cycloalkane or a ketone substance; the binder is polyisobutylene, polyethylene, polyethylene oxide, polybutadiene, polystyrene or nitrile rubber.
[0013] Preferably, the boiling point of the first solvent is between 80°C and 170°C, and the boiling point of the second solvent is at least 10°C higher than that of the first solvent.
[0014] Preferably, the mass fraction of the coated second solvent to the total amount of the first solvent and the second solvent is between 5% and 40%.
[0015] Preferably, the weight average molecular weight of the binder is between 100,000 and 3,000,000.
[0016] Preferably, the mass of the binder accounts for 1% to 6% of the mass of the electrolyte film.
[0017] Preferably, after the hot roller drying, the method further comprises: heating and drying the obtained film under vacuum conditions to remove part of the residual solvent.
[0018] Preferably, the roller temperature of the hot roller drying is between 40 and 180°C.
[0019] Preferably, the temperature of heating and drying under vacuum conditions is 98-102°C.
[0020] The present invention provides an all-solid-state battery, which comprises an electrolyte film obtained by the preparation method described above, wherein the electrolyte film has binder nanoparticles.
[0021] Compared with the prior art, the present invention firstly forms a first solvent with a high Viril coefficient and a binder, so that the molecular chain segments of the binder in the obtained first polymer solution can be fully stretched, thereby achieving the purpose of full dispersion; further, by coating and adding the second solvent, the molecular chain segments of the binder undergo a certain shrinkage and aggregation, and nanoparticles can be formed to play a preliminary bonding role; and then by hot roller pressing and drying, the gaps between the electrolyte particles are reduced, and the formed binder nanoparticles are further precipitated to exert bonding force. The present invention mainly regulates the aggregation and precipitation state of the molecular chain segments of the binder through the combination of the first solvent and the second solvent, so that the binder is distributed in the form of nano dots between the electrolyte particles, thereby relatively improving the ionic conductivity of the electrolyte film, and avoiding the problem of ion migration difficulties caused by the binder coating the surface of the electrolyte particles after the traditional wet coating and drying. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a schematic diagram of the state of materials in the process of preparing electrolyte film by traditional wet coating;
[0023] Figure 2 Schematic diagram of the state of the molecular chain segments of the binder in the preparation method of the embodiment of the present invention;
[0024] Figure 3 This is a schematic diagram of the electrolyte film forming process according to an embodiment of the present invention;
[0025] Figure 4 This is a physical picture of the state of the binder solution in Example 1 of the present invention;
[0026] Figure 5 This is a SEM image of the electrolyte film after drying according to Example 1 of the present invention;
[0027] Figure 6 This is a physical picture of the state of the binder solution in the parallel control of Example 1 of the present invention;
[0028] Figure 7 This is a SEM image of the electrolyte film after drying described in Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0029] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in combination with the drawings and the like in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] The present invention provides a method for preparing an electrolyte film for an all-solid-state battery, comprising the following steps:
[0031] S1, dissolving a binder in a first solvent to form a first polymer solution having a second Virial coefficient greater than 0;
[0032] S2, mixing the electrolyte particles with the polymer solution to form an electrolyte slurry;
[0033] S3, coating the electrolyte slurry on a substrate to form a wet film;
[0034] S4, uniformly covering the wet film with the second solvent by coating, and pressing and drying with a hot roller to obtain an electrolyte film for an all-solid-state battery;
[0035] The boiling point of the second solvent is higher than that of the first solvent. The second solvent and the first solvent are mixed to dissolve the binder to form a second polymer solution. The second Virial coefficient of the second polymer solution is smaller than the second Virial coefficient of the first polymer solution.
[0036] The method of the present invention can be used to prepare an electrolyte film with good ion conductivity, which is beneficial for application in all-solid-state batteries.
[0037] The embodiment of the present invention is mainly based on the lattice model theory of polymer solution, and regulates the stretching state of the binder in the solvent, so that the binder does not coat the electrolyte particles in the form of a film when precipitating, but is dispersed between the electrolyte particles in the form of nano-sized point particles. The traditional "face-to-face" contact between the binder and the electrolyte particles is optimized to the "point-to-point" contact in the present invention, thereby reducing the inhibitory effect of the binder on lithium ions and improving the ionic conductivity of the electrolyte film to a certain extent.
[0038] Specifically, according to the lattice model theory of polymer solution, the formula for the second Virial coefficient of polymer solution is as follows:
[0039]
[0040] Where v1° is the specific volume of the binder, V0° is the molar volume of the pure solvent, and x is the interaction parameter between the binder and the solvent.
[0041] According to the description of the lattice model theory and the second Virial coefficient, when A2>0, the molecular chain segments of the binder dispersed in the solvent are mainly repulsive, and the molecular chain segments are in a stretched expansion state. When A2<0, the molecular chain segments of the binder dispersed in the solvent are mainly attractive, and the molecular chain segments are in a curled contraction state.
[0042] The embodiment of the present invention utilizes the characteristic that the polymer solution conforms to the lattice model theory within a certain concentration range, and adjusts the interaction parameter x between the binder and the solvent, so that the binder molecular chain segments are in different stretch-contraction states at different stages of the preparation of the electrolyte film. Thus, the binder molecular chain segments can be fully dispersed in the electrolyte particles and the solvent, and can be precipitated in an ideal particle size and morphology.
[0043] The interaction parameter x between the binder and the solvent is related to the properties of the binder and the solvent itself, that is, the molecular weight, degree of polymerization, and bonding type of the binder. It is also related to the molecular structure of the binder itself. Therefore, the same binder has different x in different solvents.
[0044] The embodiment of the present invention mainly uses a binder B, a first solvent S1 and a second solvent S2 to achieve the above purpose. The specific operation process is as follows (for ease of description, the binder can be represented by B, and the solvents can be represented by S1 and S2):
[0045] 1. Dissolve the binder in the first solvent S1 to form a binder solution, namely the first polymer solution M1, which is in a clear solution state.
[0046] The properties required of the binder B and the first solvent S1 are to make the second Virial coefficient A2 of the M1 polymer solution greater than 0, so that in this step, the binder molecular segments can be fully stretched and dispersed, and fully dissolved in the solvent to form a stable polymer solution. If the first solvent and the second solvent are added at the same time, the binder molecular segments cannot be fully dispersed.
[0047] 2. The electrolyte particles and the polymer solution M1 can be mixed and homogenized to prepare an electrolyte slurry.
[0048] 3. Apply the above electrolyte slurry on the substrate to form a wet film.
[0049] 4. The second solvent S2 can be gradually covered on the wet film of step 3 by spraying. In this step, the second solvent S2 is used, which can be mixed with the first solvent S1 to dissolve the binder B to form a second polymer solution M2. S2 has the following characteristics: a. S2 and S1 are miscible and can form a miscible body; b. The second Virial coefficient A2' between the solvent S2+S1 and B is less than the second Virial coefficient A2 between S1 and B; c. The boiling point of S2 is higher than the boiling point of S1.
[0050] Based on the above two characteristics a to b, the binder molecular chain segments that were originally in a stretched state in the slurry composed of solvent S1 are actually in the mixed solvent composed of S1 + S2 after the addition of S2. However, the second virial coefficient between the (S1 + S2) solvent and B decreases with the addition of S2 due to the aforementioned A2’ < A2. Therefore, the stretched state of the binder molecular chain segments in the slurry changes accordingly. As the addition amount of S2 increases, the degree of shrinkage of the B molecular chain segments gradually increases. Therefore, the B chain segments gradually form aggregated particles with a nanoscale size. With the precipitation of the aggregated particles, a certain adhesive force is formed between the binder B among the electrolyte particles, and at the same time, the polymer solution of B gradually transforms into a sol.
[0051] 5. The sprayed wet film in the above step 4 is repeatedly and gradually roll-pressed in a heated pair of rollers. Since the boiling point of S1 is lower than that of S2, that is, the saturated vapor pressure of S1 is higher than that of S2, during the heating process, the volatilization rate of S1 is greater than that of S2. Therefore, the second virial coefficient between the mixed solvent (S1 + S2) and the binder B continuously increases, and the B molecular chain segments are gradually precipitated in the form of nanoparticles between the electrolyte particles during the roll-pressing process, playing a binding role between the electrolyte particles. The treatment effects of the foregoing steps are as Figure 2 shown, successively including: the molecular chain segments are in a dispersed and stretched state; the molecular chain segments contract and begin to aggregate; the degree of contraction and aggregation of the molecular chain segments increases.
[0052] At the same time, another technical effect that can be achieved by this step is that there is liquid between the electrolyte particles, which can sufficiently reduce the frictional resistance between the electrolyte particles. Therefore, compared with the roll-pressing of the dried electrolyte film, this step can further reduce the porosity of the film and make the contact between the electrolyte particles closer.
[0053] 6. The present invention preferably further heats and dries the film after hot roll-pressing in a vacuum condition to remove the remaining part of the solvent. Since the boiling point of S1 is lower than that of S2, and S1 has volatilized preferentially more than S2 in step 5, the B that has already precipitated as nanoparticles in this heating step will not dissolve in S1 to form a solution with stretched chain segments and precipitate as a film-like coating; this is also another reason for controlling the boiling point of S2 to be higher than that of S1 in the present invention.
[0054] The film-forming process of the electrolyte is as Figure 3 shown, successively being the slurry state, the wet film state, and the dry state. It can be seen that due to the regulation of the curled state of the binder molecular chain segments, the final binder precipitates on the surface of the electrolyte particles in the form of particles, avoiding the binder presenting a planar coating on the surface of the electrolyte particles as in the traditional wet coating method.
[0055] From the above discussion, it can be seen that the key to the present invention is to adjust the second Virial coefficient between the solvent and the binder B by adjusting the combination and proportion of the solvents S1 and S2, so that the binder presents a controllable stretch-contraction state in different preparation processes of the electrolyte film, thereby ultimately achieving nanoscale point precipitation and playing a bonding effect.
[0056] Among them, the second Virial coefficient is closely related to the type of binder B itself, the type and mixing ratio of organic solvents S1 and S2. Therefore, in order to achieve the purpose of the present invention, the selection of S1, S2, and B is not conventionally determined by a single variable, but a combination of the three based on the principle of regulation and synergistic effect. At the same time, in order to ensure the stability between the solvent and the electrolyte, the solvent is preferably a low-polarity or non-polar solvent. The first solvent S1 is preferably a substituted or unsubstituted aromatic hydrocarbon substance, an amide substance or a sulfoxide substance (a class of compounds containing sulfinyl groups), for example, S1 can be: benzene, toluene, monochlorobenzene, biphenyl, methylformamide or dimethyl sulfoxide; the corresponding B can be: polyisobutylene, polyethylene, polyethylene oxide, polybutadiene, polystyrene or nitrile rubber. The corresponding second solvent S2 is preferably a straight-chain alkane, a cycloalkane or a ketone substance, for example, S2 can be: cyclohexane, n-heptane, n-hexane, acetophenone or benzophenone.
[0057] When used in combination in some embodiments of the present invention, the boiling point of S1 is between 80 and 170° C., and the boiling point of S2 is 10 to 30° C. higher than that of S1. The molecular weight Mw of the binder B is between 100,000 and 3 million, and can further be between 200,000 and 2 million.
[0058] The electrolyte particles described in the embodiment of the present invention can be inorganic solid electrolytes such as sulfides, halides, oxides, etc., such as Li6PS5Cl, Li7P3S 11 , Li3PS4, Li2ZrCl6, Li7La3Zr2O 12 , Li 1.3 Al 0.3 Ti 1.7 (PO4)3; the conductivity of the electrolyte powder should be higher than 0.1mS / cm. The electrolyte and the first polymer solution M1 are mixed with a homogenizer to prepare an electrolyte slurry, and the solid content of the slurry is preferably 40-50%. Preferably, the binder B accounts for 1-6% of the total solid mass, and further 2-5%.
[0059] In the embodiment of the present invention, the obtained electrolyte slurry is coated on a substrate to form a wet film; the present invention has no special restrictions on the coating, and the coating thickness is preferably 40 microns. The coating method can be blade coating, extrusion coating, comma roller coating; the coating substrate can be copper foil, aluminum foil, stainless steel foil, tin foil, etc.
[0060] In an embodiment of the present invention, the second solvent S2 is preferably sprayed to gradually and evenly cover the wet film formed in the above steps. In the spraying step, the mass fraction of S2 in the total solvent is between 5% and 40%, and can further be 10% to 30%.
[0061] In the step of hot roller drying after spraying in the embodiment of the present invention, the roller temperature is preferably between 40 and 180°C. In the preferred embodiment of the present invention, the wet film after spraying can be rolled at a distance of 38 microns in a roller machine at a temperature of 40 to 60°C. Then the temperature is raised to 60 to 100°C, and the film is rolled at a distance of 36 microns; then the temperature is raised to 70 to 180°C, and the film is rolled at a distance of 34 microns. That is, it is preferred to gradually increase the temperature and reduce the distance, so that the first solvent S1 and the second solvent S2 gradually evaporate, and the binder B gradually precipitates, while ensuring that the solvent remains in the gap between the electrolyte particles, which plays a compacting lubrication effect.
[0062] In the embodiment of the present invention, the film after hot roller drying can be heated and dried at -0.1Mpa and 98-102°C to remove the residual solvent, thereby obtaining an electrolyte film for an all-solid-state battery. In the electrolyte film described in the embodiment of the present invention, the precipitated binder B is in the form of nano-sized particles on the surface of the electrolyte particles; the ionic conductivity of the dried electrolyte film is relatively high.
[0063] The present invention also provides an all-solid-state battery, which includes the electrolyte film obtained by the preparation method described above. The embodiment of the present invention has no special restrictions on other components of the all-solid-state battery. Based on the good characteristics of the electrolyte film, the performance of the all-solid-state battery is improved.
[0064] In order to better illustrate the present invention, the following examples are further illustrated. Unless otherwise specified, the various reagents and raw materials used in the present invention are all commercially available products or products that can be prepared by recognized methods. Unless otherwise specified, the ratios involved are all mass ratios.
[0065] Example 1
[0066] The specific operation process is as follows:
[0067] 1. Dissolve the binder polyisobutylene with a molecular weight Mw of 565,000 in the first solvent benzene (boiling point is about 80°C) to form a binder solution M1. Figure 4 As shown, it is a clear solution state.
[0068] 2. The sulfide electrolyte particles Li6PS5Cl were mixed with the above solution M1 using a homogenizer to prepare an electrolyte slurry with a solid content of 45%; the binder accounted for 5% of the total solid content.
[0069] 3. The above electrolyte slurry was conventionally coated on tin foil to form a wet film with a coating thickness of 40 μm.
[0070] 4. Spray the second solvent n-heptane (boiling point is about 98° C.) onto the wet film in step 3 step by step. The spraying amount of n-heptane accounts for 25% of the total solvent mass; and pre-dry at 60° C. for 30 minutes.
[0071] 5. The wet film after spraying is rolled in a roller machine at a temperature of 60°C and at a distance of 38 microns. Then the temperature is raised to 70°C and rolled at a distance of 36 microns; then the temperature is raised to 75°C and rolled at a distance of 34 microns.
[0072] 6. After being pressed by a hot roller, the film was heated and dried at -0.1 MPa and 100° C. for 2 h to remove the remaining solvent and obtain a dry electrolyte film.
[0073] After the electrolyte film was dried, the surface of the electrolyte particles was characterized using a scanning electron microscope (SEM). Figure 5 As shown, it can be seen that the binder is precipitated in the form of nano-sized particles on the surface of the electrolyte particles.
[0074] At the same time, in order to illustrate the effect of the addition of the second solvent on the agglomeration effect of the binder molecular segments, in particular, a parallel sample was prepared in step 1, and the second solvent of the same dosage as in step 4 was added dropwise to the binder solution formed therefrom. After addition, the state of the solvent is as follows: Figure 6 As shown. Unlike the clarified binder solution in step 1, Figure 6 The liquid in the solution exhibits an obvious Tyndall effect, which means that with the addition of the second solvent, the molecular segments of the binder can shrink and be evenly distributed in the solvent in the form of nano-sized particles.
[0075] Example 2
[0076] The specific operation process is as follows:
[0077] 1. Dissolve the binder polyisobutylene with a molecular weight Mw of 565,000 in the first solvent toluene (boiling point of about 110.6° C.) to form a binder solution M1.
[0078] 2. The sulfide electrolyte particles Li6PS5Cl were mixed with the above solution M1 using a homogenizer to prepare an electrolyte slurry with a solid content of 45%; the binder accounted for 5% of the total solid content.
[0079] 3. Apply the above electrolyte slurry on tin foil to form a wet film with a coating thickness of 40 microns.
[0080] 4. The second solvent 3-dichloropropane (boiling point about 125°C) is gradually sprayed on the wet film in step 3. The spraying amount of n-heptane accounts for 25% of the total solvent mass. Pre-dry at 90°C for 30 minutes.
[0081] 5. The wet film after spraying is rolled in a roller machine at a temperature of 95°C with a gap of 38 microns. Then the temperature is raised to 100°C and rolled at a gap of 36 microns; then the temperature is raised to 105°C and rolled at a gap of 34 microns.
[0082] 6. After being pressed by a hot roller, the film was heated and dried at -0.1 MPa and 125° C. for 2 h to remove the remaining solvent and obtain a dry electrolyte film.
[0083] Example 3
[0084] The specific operation process is as follows:
[0085] 1. Dissolve the binder polyisobutylene with a molecular weight Mw of 1100000 in the first solvent benzene (boiling point 80° C.) to form a binder solution M1.
[0086] 2. The sulfide electrolyte particles Li6PS5Cl were mixed with the above solution M1 using a homogenizer to prepare an electrolyte slurry with a solid content of 45%; the binder accounted for 5% of the total solid content.
[0087] 3. Apply the above electrolyte slurry on tin foil to form a wet film with a coating thickness of 40 microns.
[0088] 4. Spray the second solvent n-heptane (boiling point about 98°C) gradually over the wet film in step 3. The spraying amount of n-heptane accounts for 25% of the total solvent mass. Pre-dry at 60°C for 30 minutes.
[0089] 5. The wet film after spraying is rolled in a roller machine at a temperature of 60°C and at a distance of 38 microns. Then the temperature is raised to 70°C and rolled at a distance of 36 microns; then the temperature is raised to 75°C and rolled at a distance of 34 microns.
[0090] 6. After being pressed by a hot roller, the film was heated and dried at -0.1 MPa and 125° C. for 2 h to remove the remaining solvent and obtain a dry electrolyte film.
[0091] Example 4
[0092] The specific operation process is as follows:
[0093] 1. Dissolve the binder polyethylene with a molecular weight Mw of 1500000 in the first solvent toluene (boiling point about 110.6° C.) to form a binder solution M1.
[0094] 2. The sulfide electrolyte particles Li6PS5Cl were mixed with the above solution M1 using a homogenizer to prepare an electrolyte slurry with a solid content of 45%; the binder accounted for 6% of the total solid content.
[0095] 3. Apply the above electrolyte slurry on tin foil to form a wet film with a coating thickness of 40 microns.
[0096] 4. The second solvent 3-dichloropropane (boiling point about 125°C) is gradually sprayed on the wet film in step 3. The spraying amount of n-heptane accounts for 25% of the total solvent mass. Pre-dry at 90°C for 30 minutes.
[0097] 5. The wet film after spraying is rolled in a roller machine at a temperature of 95°C with a gap of 38 microns. Then the temperature is raised to 100°C and rolled at a gap of 36 microns; then the temperature is raised to 105°C and rolled at a gap of 34 microns.
[0098] 6. After being pressed by a hot roller, the film was heated and dried at -0.1 MPa and 125° C. for 2 h to remove the remaining solvent and obtain a dry electrolyte film.
[0099] Example 5
[0100] The specific operation process is as follows:
[0101] 1. Dissolve the binder polyisobutylene with a molecular weight Mw of 565,000 in the first solvent benzene (boiling point 80° C.) to form a binder solution M1.
[0102] 2. The sulfide electrolyte particles Li6PS5Cl were mixed with the above solution M1 using a homogenizer to prepare an electrolyte slurry with a solid content of 40%; the binder accounted for 5% of the total solid content.
[0103] 3. The above electrolyte slurry was coated on the aluminum foil to form a wet film with a coating thickness of 40 μm.
[0104] 4. Spray the second solvent n-heptane (boiling point about 98°C) gradually over the wet film in step 3. The spraying amount of n-heptane accounts for 5% of the total solvent mass. Pre-dry at 60°C for 30 minutes.
[0105] 5. The wet film after spraying is rolled in a roller machine at a temperature of 60°C and at a distance of 38 microns. Then the temperature is raised to 70°C and rolled at a distance of 36 microns; then the temperature is raised to 75°C and rolled at a distance of 34 microns.
[0106] 6. After being pressed by a hot roller, the film was heated and dried at -0.1 MPa and 125° C. for 2 h to remove the remaining solvent and obtain a dry electrolyte film.
[0107] Example 6
[0108] The specific operation process is as follows:
[0109] 1. Dissolve the binder polyisobutylene with a molecular weight Mw of 565,000 in the first solvent benzene (boiling point 80° C.) to form a binder solution M1.
[0110] 2. The sulfide electrolyte particles Li6PS5Cl were mixed with the above solution M1 using a homogenizer to prepare an electrolyte slurry with a solid content of 50%; the binder accounted for 5% of the total solid content.
[0111] 3. The above electrolyte slurry was coated on the aluminum foil to form a wet film with a coating thickness of 40 μm.
[0112] 4. Spray the second solvent n-heptane (boiling point about 98°C) gradually over the wet film in step 3. The spraying amount of n-heptane accounts for 40% of the total solvent mass. Pre-dry at 60°C for 30 minutes.
[0113] 5. The wet film after spraying is rolled in a roller machine at a temperature of 60°C and at a distance of 38 microns. Then the temperature is raised to 70°C and rolled at a distance of 36 microns; then the temperature is raised to 75°C and rolled at a distance of 34 microns.
[0114] 6. After being pressed by a hot roller, the film was heated and dried at -0.1 MPa and 125° C. for 2 h to remove the remaining solvent and obtain a dry electrolyte film.
[0115] Example 7
[0116] The specific operation process is as follows:
[0117] 1. Dissolve the binder nitrile rubber with a molecular weight Mw of 2800000 in the first solvent ethyl butyrate (boiling point 120° C.) to form a binder solution M1.
[0118] 2. The sulfide electrolyte particles Li6PS5Cl were mixed with the above solution M1 using a homogenizer to prepare an electrolyte slurry with a solid content of 45%; the binder accounted for 2% of the total solid content.
[0119] 3. The above electrolyte slurry was coated on the aluminum foil to form a wet film with a coating thickness of 40 μm.
[0120] 4. Spray the second solvent diethylene glycol dimethyl ether (boiling point 159.7°C) onto the wet film in step 3 step by step. The spraying amount of n-heptane accounts for 25% of the total solvent mass. Pre-dry at 100°C for 30 minutes.
[0121] 5. The wet film after spraying is rolled in a roller machine at a temperature of 100°C with a gap of 38 microns. Then the temperature is raised to 105°C and rolled at a gap of 36 microns; then the temperature is raised to 110°C and rolled at a gap of 34 microns.
[0122] 6. After being pressed by a hot roller, the film was heated and dried at -0.1 MPa and 125° C. for 2 h to remove the remaining solvent and obtain a dry electrolyte film.
[0123] Comparative Example 1
[0124] 1. Dissolve the binder polyisobutylene with a molecular weight Mw of 565,000 in the solvent benzene to form a binder solution M1.
[0125] 2. The sulfide electrolyte particles Li6PS5Cl were mixed with the above solution M1 using a homogenizer to prepare an electrolyte slurry; the solid content of the slurry was 45%, and the binder accounted for 5% of the total solid content.
[0126] 3. Apply the above electrolyte slurry on tin foil to form a wet film with a coating thickness of 40 microns.
[0127] 4. The wet film was heated and dried at -0.1 MPa and 80°C for 2 h to remove the remaining solvent and obtain an electrolyte film.
[0128] After the electrolyte film was dried, the surface of the electrolyte particles was characterized using a scanning electron microscope. Figure 7 shown.
[0129] It can be seen that the surface of the electrolyte particles in Comparative Example 1 is significantly different from the surface of Example 1. In Comparative Example 1, the binder is precipitated in a coated state on the surface of the electrolyte particles, wrapping the electrolyte in the binder. Rather than a point-like precipitation similar to that in Example 1. At the same time, although the test acceleration voltage of the SEM in Comparative Example 1 is the same as that in Example 1, the image in Comparative Example 1 is more blurred. This is because, if the conductivity of the sample is better, the electron beam can be evenly scattered on the surface of the sample, thereby forming a clear image. However, if the conductivity of the sample deteriorates, the electron beam will be attracted and focused by the surface charge, resulting in blurred or distorted images. This shows that in Comparative Example 1, the planar coating of the binder causes the conductivity of the sample to decrease, which is also consistent with the test results of ionic conductivity.
[0130] The above electrolyte film was cut into discs with a diameter of 10 mm, placed in a mold with an inner diameter of 10 mm, a pressure of 200 MPa was applied, and an AC impedance meter was used for testing.
[0131] The ionic conductivity test results of each electrolyte film are shown in the following table:
[0132] Table 1 Ionic conductivity of electrolyte membranes of Example 1 of the present invention and Comparative Example 1
[0133] serial number Ionic conductivity (mS / cm) Blank sample (electrolyte powder) 3.7 Example 1 2.26 Example 2 2.03 Example 3 1.59 Example 4 1.26 Example 5 0.95 Example 6 2.44 Example 7 1.82 Comparative Example 1 0.42
[0134] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing an electrolyte film for an all-solid-state battery, characterized in that: The following steps are involved: dissolving a binder in a first solvent to form a first polymer solution having a second Virial coefficient greater than 0; mixing electrolyte particles with the polymer solution to form an electrolyte slurry; coating the electrolyte slurry on a substrate to form a wet film; The second solvent is evenly coated on the wet film by coating, and then pressed dry by a hot roller to obtain an electrolyte film for an all-solid-state battery; The boiling point of the second solvent is higher than that of the first solvent. The second solvent and the first solvent are mixed to dissolve the binder to form a second polymer solution. The second Virial coefficient of the second polymer solution is smaller than the second Virial coefficient of the first polymer solution.
2. The preparation method according to claim 1, characterized in that: The first solvent and the second solvent are both low-polar or non-polar organic solvents; the first solvent is a substituted or unsubstituted aromatic hydrocarbon substance, an amide substance or a sulfoxide substance; the second solvent is a straight-chain alkane, a cycloalkane or a ketone substance; the binder is polyisobutylene, polyethylene, polyethylene oxide, polybutadiene, polystyrene or nitrile rubber.
3. The preparation method according to claim 1, characterized in that: The boiling point of the first solvent is between 80° C. and 170° C., and the boiling point of the second solvent is at least 10° C. higher than that of the first solvent.
4. The preparation method according to claim 3, characterized in that: The mass fraction of the coated second solvent to the total amount of the first solvent and the second solvent is between 5% and 40%.
5. The preparation method according to any one of claims 1 to 4, characterized in that: The weight average molecular weight of the binder is between 100,000 and 3,000,000.
6. The preparation method according to claim 5, characterized in that: The mass of the binder accounts for 1% to 6% of the mass of the electrolyte film.
7. The preparation method according to any one of claims 1 to 4, characterized in that: After the hot roller drying, the method further includes: heating and drying the obtained film under vacuum conditions to remove part of the residual solvent.
8. The preparation method according to claim 7, characterized in that: The roller temperature of the hot roller pressing is between 40 and 180°C.
9. The preparation method according to claim 8, characterized in that: The temperature of heating and drying under the vacuum condition is 98-102°C.
10. An all-solid-state battery, characterized in that: An electrolyte film obtained by the preparation method according to any one of claims 1 to 9, wherein the electrolyte film contains binder nanoparticles.
Citation Information
Cited By
Electrolyte thin film and preparation method therefor
WO2026174465A1